How to create indices for bank branch financial performance measurement using MCDA techniques: an illustrative example - Ferreira, Fernando A. F.; Santos, Sérgio P.; Santos, Paulo M. M.; Spahr, Ronald W. (Journal of Business Economics and Management, 2014)
Most banks have been negatively affected by the recent economic recession, which has forced them to evaluate their operating performance including the financial performance of bank branches. Approaches that have been applied to address the financial performance evaluation of bank branches include: optimization techniques, simulations, stochastic tools, fuzzy logics and decision support systems. Although recent improvements have been made in assessing financial performance, the potential for significant further improvement remains since the recent world economic crisis is adding pressure on business margins. The purpose of this paper is to construct an exemplificative evaluation index for bank branch financial performance by integrating cognitive maps with measuring attractiveness by a categorical based evaluation technique. We aim to apply this methodology constructively to serve as a learning mechanism and introduce transparency in the decision making process. Practical applications, strengths and weaknesses of the proposed evaluation index are also discussed.